MEDICAL EMERGENCY TEAM AS AN ACCIDENTAL WITNESS TO THE RITUAL OF EXORCISM PERFORMED ON A PREGNANT MUSLIM WOMAN - Simić, Vladimir; Andjelic, Sladjana; Nikolic, Bojan; Milosavljevic, Goran; Vukicevic, Verica (Halo 194 Scientific Journal of Emergency Medicine, 2023)
We present a religious ritual of exorcism performed by a Muslim priest of a pregnant woman of the Islamic faith in the third month of pregnancy with body twitches and abdominal pain, in which emergency medical services (EMS) team was an accidental witness.